An investigation of Al2O3 coating on quartz fiber fabric in aqueous solution near room temperature. Issue 4 (11th May 2022) - Zhang, Yongfu; Xiang, Yan; Yang, Yunjie; Wei, Xiaolin; Ma, Ben; Chen, Weiwei; Cheng, Huanwu; Wang, Lu; Lu, Lin; Li, Maoyuan; Fu, Haifeng
Abstract : Quartz fiber fabric is widely used in national defense, military and aerospace industries due to its good high-temperature resistance, chemical stability and excellent thermal shock resistance. However, the tendency of quartz fiber fabric to undergo thermal degradation due to crystallization at high temperature may destroy its high-temperature performance, particularly its high-temperature mechanical properties. In this study, an aluminum oxide (Al2 O3 ) ceramic coating was synthesized on the surface of two-dimensional quartz fiber fabric in aqueous solution near room temperature. The surface morphology and chemical composition were studied to evaluate the quality of the coating by scanning electron microscopy, atomic force microscopy, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. The annealing behavior at high temperature was evaluated by using an electronic universal testing machine after high-temperature processing. The annealing behavior of the aluminum oxide coating could be improved effectively. The maximum load that the coated fabric can bear was 2.5 times higher than that of the original fabric, proving the superior high-temperature mechanical properties of the coated fabric. The coating on the surface of the fiber could block the damage of high temperature to the quartz fiber, improving the crystallization phenomenon of the quartz fiber at high temperature, followed by improvement in the high-temperature mechanical properties of the fabric.